RESPONS MORFOLOGI DAN PRODUKSI CABAI RAWIT (Capsicum frutescens L.) TERHADAP INDUKSI POLIPLOIDI DENGAN KOLKISIN - Astutik Astutik; Astri Sumiati; Susilo Ribut Anggarbeni; Maftuh P.D.K. (BUANA SAINS, 2025)
Polyploidy induction is a plant breeding strategy to improve agronomic traits. This study aimed to examine the effect of colchicine concentration and immersion duration on the morphological, phenological, and production characteristics of cayenne pepper (Capsicum frutescens L.). The experiment used a Factorial Randomized Block Design with two factors: colchicine concentration (0, 10, 20, 30 ppm) and immersion duration (12, 24 hours), replicated four times. Data were analyzed using two-way ANOVA and the least Significant Difference (LSD) test at ?=5%. The results showed a significant interaction between both factors on plant height, leaf area, flowering time, fruit length, and flesh thickness. The 30 ppm colchicine with 24-hour immersion (K3W2) produced the widest leaves (7.98 cm) but delayed flowering initiation to 80 days after planting (DAP). The highest yield (7.2 tons/ha) was achieved at K3W2, showing a 92% increase compared to the control. Indicated polyploidy resulted in shorter fruits (4.32 cm) but with larger diameter (1.35 cm), thicker flesh (0.044 cm), and fewer seeds (53.75 seeds/fruit). It is concluded that 30 ppm colchicine effectively induces polyploid phenotypic changes in cayenne pepper, increasing yield but reducing generative fertility.